PENGARUH KARAKTERISTIKPEKERJAAN, BEBAN KERJA, STRES KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK MADYA MEDAN - Siska Syahvitri (JRMB (Jurnal Riset Manajemen & Bisnis), 2020)
The problem in this research are: How does the effect of job characteristics on employee performance in Medan Intermediate Tax Service Office. How does work influence affect employee performance, how does work stress affect employee performance, how does motivation influence employee performance, how does work characteristics influence, burden work, work stress and motivation on employee performance. The proposed hypothesis is: Job characteristics have positive and significant effect on employee performance, workload has positive and not significant effect on employee performance, work stress has a positive and not significant effect on employee performance, motivation has a positive and significant effect on employee performance, Job characteristics, burden work, work stress and motivation have a positive and significant effect on employee performance at the Medan Intermediate Tax Service Office. " The study was conducted at Medan Intermediate Tax Service Office. Jalan Sukamulia No. 17-A, Medan, with a sample of 95 people. Based on the analysis results obtained t value for job characteristics = 7.151, while t-table with dk 95 (Appendix) of 1.66, then t count t-table thus there is a positive influence between job characteristics on employee performance (Hypothesis 1 accepted) The value of t workload = -0.868, while the t-table with dk 95 (Appendix) is 1.66, then t arithmetic ˂ t table thus partially there is a negative influence between workload on employee performance (Hypothesis 2 is accepted). t work stress = -0.105, while t-table with dk 95 (Appendix) of 1.66, then t arithmetic ˂ t table thus partially there is a negative influence between work stress on employee performance Thus hypothesis 3 is accepted as correct. Motivation t value = 2.110, while t-table with dk 95 (Appendix) is 1.66, then t arithmetic ˃ t table thus partially there is a negative influence between work stress on employee performance. Thus hypothesis 4 is accepted as true. The F-count value is 16.502 while the F-table value (Appendix) with the numerator dk 4 and the denominator dk 90 is 2.46 where F-count F table (16.502 2.46) then it can be mentioned that together ( multiple) there is a positive and significant influence of job characteristics, workload, work stress and motivation on employee performance. Thus the hypothesis 5 submitted accepted the truth.